HUBUNGAN RESPON TIME PERAWAT DENGAN TINGKAT KEPUASAN PASIEN DI IGD RUMAH SAKIT AN-NISA TANGERANG - siti mulkilah mul (Jurnal Riset Media Keperawatan, 2026)
Fast and responsive nursing care plays an important role in creating patient satisfaction, especially in the Emergency Department (ED). Nurses’ response time is one of the quality service indicators that can influence patients’ perceptions of hospital service quality. to determine the relationship between nurses’ response time and the level of patient satisfaction in the Emergency Department of An-Nisa Hospital, Tangerang. this study used a quantitative method with a cross-sectional approach. The sample in this study consisted of 349 respondents selected using purposive sampling technique. Data were collected through a questionnaire on patient satisfaction and an observation sheet on response time. The analysis using Spearman Rho test showed a significant relationship between nurses’ response time and patient satisfaction level (p-Value < 0.001). Keywords: respon time, patient satisfaction, emergency departement